Challenges in Using Communicative English Proficiency: A Study on Academic Writing of DEE UMS Students - Tsalsabilla, Fadia Aurilly; Laila, Malikatul; Fauziati, Endang (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to examine the challenges faced by English Education students at Universitas Muhammadiyah Surakarta in achieving formal language proficiency, with a particular emphasis on vocabulary development as a crucial component of communicative English proficiency in academic writing. The research seeks to identify how vocabulary limitations hinder students' ability to construct formal, accurate, and contextually appropriate expressions in their essays. Methodology: This study analyzes ten student essays purposively selected from academic writing tasks. The analysis framework was adapted from Hymes' (1972) and Canale and Swain's (1980) communicative competence model, focusing on clarity, vocabulary use, formal register, and identified challenges.Results: Findings indicate that students generally demonstrate communicative clarity but struggle with lexical depth and formality. While their ideas are coherently expressed, most rely on basic vocabulary and exhibit inconsistent control over academic register. Occasional attempts at lexical sophistication were observed but were not consistently sustained, reflecting transitional proficiency between informal and academic discourse. Applications/Originality/Value: This study highlights the essential role of vocabulary enrichment and register awareness in developing communicative proficiency in academic writing. Its originality lies in analysing how vocabulary-related challenges specifically affect students' ability to use English formally in written contexts, offering pedagogical insights for enhancing academic vocabulary instruction and formal writing competence in higher education.